1977
DOI: 10.2307/1589324
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response of Chickens Exposed to a Type 1 Avian Adenovirus Alone or in Combination with the Adeno-Associated Virus

Abstract: The avian adenoviruses (AV) are common infectious agents of poultry and other avian species throughout the world (1,4,8). Limited observations suggest that the adeno-associated virus (A-AV) coinfects many of the chickens that carry AV (8). The presence and persistence of these infections in a flock is often determined by serological methods. In the current study, the immune response of chickens to type 1 AV alone and to a dual exposure, AV plus A-AV, was followed over a 12-week period with a variety of serolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…They are generally considered nonpathogenic, although some serotypes have been associated with reproductive abnormalities in humans and others have been shown to modify cell cycle progression in vitro, either inducing apoptosis or inhibiting it (25,35,43). In birds, latent infections are widespread, and several studies have suggested that AAV can modify humoral immunity and the pathogenicity of adenovirus infections in vivo (39,57). Our data showed no correlation between the severity or distribution of lesions in falcons and the presence of AAV or a particular genotype of AAV.…”
Section: Discussionmentioning
confidence: 99%
“…They are generally considered nonpathogenic, although some serotypes have been associated with reproductive abnormalities in humans and others have been shown to modify cell cycle progression in vitro, either inducing apoptosis or inhibiting it (25,35,43). In birds, latent infections are widespread, and several studies have suggested that AAV can modify humoral immunity and the pathogenicity of adenovirus infections in vivo (39,57). Our data showed no correlation between the severity or distribution of lesions in falcons and the presence of AAV or a particular genotype of AAV.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, a different study found that it was possible to reinfect chickens with the same strain after 8 weeks. 29 To be able to make appropriate decisions, it is important to determine whether chickens naturally invaded by a primary FAV infection develop resistance to reinfection.…”
mentioning
confidence: 99%
“…Thus Burke et al (1959) The DID test has been used for diagnosis and monitoring of specific pathogenfree (SPF) flocks for infection. This observation has been confirmed by others (Grimes et al, 1977a;Yates et al, 1977). McFerran et al (1975) drew attention to the failure of SPF birds experimentally infected by a natural route with one serotype always to develop detectable antibody.…”
Section: Diagnosismentioning
confidence: 53%